TEDAS - Tail Event Driven ASset Allocation - Wolfgang Karl Härdle; Sergey Nasekin; David Kuo Chuen Lee; Phoon Kok Fai (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
Portfolio selection and risk management are very actively studied topics in quantitative finance and applied statistics. They are closely related to the dependency structure of portfolio assets or risk factors. The correlation structure across assets and opposite tail movements are essential to the asset allocation problem, since they determine the level of risk in a position. Correlation alone is not informative on the distributional details of the assets. By introducing TEDAS -Tail Event Driven ASset allocation, one studies the dependence between assets at different quantiles. In a hedging exercise, TEDAS uses adaptive Lasso based quantile regression in order to determine an active set of negative non-zero coefficients. Based on these active risk factors, an adjustment for intertemporal correlation is made. Finally, the asset allocation weights are determined via a Cornish-Fisher Value-at-Risk optimization. TEDAS is studied in simulation and a practical utility-based example using hedge fund indices.
Keywords: C00; C14; C50; C58; 330; Portfolio optimization; asset allocation; adaptive lasso; quantile regression; value-at-risk